Strategi Keberlanjutan Program Bank Sampah di Kabupaten Jember dengan Analisis SWOT - Ririn Agustini; Khoiron Khoiron; Farida Wahyu Ningtyias (ARTERI : Jurnal Ilmu Kesehatan, 2025)
The Waste Bank program in Jember Regency is currently performing suboptimally, as evidenced by the annual decline in the number of Waste Banks. Low activity levels significantly hinder the effectiveness of waste reduction at the source.: This study aimed to analyze sustainability strategies for the Waste Bank program in Jember Regency using SWOT analysis. A quantitative descriptive research design was employed. A sample of 36 Waste Banks located in three districts was selected using simple random sampling. The subjects were Waste Bank managers. Primary data were collected through interviews using questionnaires aligned with Ministry of Environment regulations, while secondary data were obtained from the Jember Regency Environmental Agency regarding the number of Waste Banks. Results: The SWOT matrix analysis placed the program in Quadrant III, indicating a critical need to address internal weaknesses while leveraging market opportunities. Conclusion & Priority strategies are recommended as follows: 1) Financial: expanding funding sources through partnerships with the government, private sector, financial institutions, and Corporate Social Responsibility (CSR) programs; 2) Human Resources: collaborating with universities, schools, and environmental communities to strengthen capacity through internships, research, and community service-based training; 3) Market: producing processed products from organic and inorganic waste, creating innovative programs, and enhancing service branding; and 4) Legal: establishing local regulations regarding the Waste Bank program and encouraging private sector involvement via CSR to support financing, training, and infrastructure provision.